The critique of feminism on traditional Christian theology: an analysis from Qur’ānic perspective - Abdul Rahim, Adibah; Ahmad, Nadzrah (USIM Press, 2019)
The study attempts to highlight feminists’ critics against traditional Christian theology on women. Traditional Cristian theology or known as Biblical or Christian patriarchy by the feminists has allegedly been studied and comprehended from a patriarchal perspective of male dominance hence misrepresentation of female scriptural image within the Bible. In this study, feminists’ critics on issue pertaining to women in the Bible were selected and analyzed its specifics before scrutinized further from Qur’anic point of view. The study finds that despite the feminists’ claim of image defamation of women in the Bible, the Qur’ān on the other hand represented its female subjects in the most acceptable non- discriminative manner. Women as depicted in the Qur’ān were purged of any offensive and denounced outcomes of their own existence and nature. Utilizing scriptural-textual analysis method, the study embarks on deriving points of comparison between the two scriptures highlighting agreements and discrepancies of both texts.